Legal Uncertainty and Its Implications for Innovation and Equality in Ride-Hailing - Siti Mariyam; Arowosaiye, Yusuf Ibrahim; Markus Suryoutomo; Agus Wibowo (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
Transportation plays a vital role in national development and public welfare. However, regulating ride-hailing in Indonesia encounters significant challenges, particularly regarding legal certainty and fairness. This study investigates the complexity of legal uncertainty and inequality within the partnership framework of ride-hailing services. Using a normative legal approach comprising legislative, conceptual, and comparative methods, the study finds that overlapping laws, lack of uniform operational standards, and inconsistent law enforcement create legal ambiguity. Moreover, it identifies systemic inequalities in the ride-hailing partnership model, where drivers are in a structurally weaker position than platform companies. These imbalances are inadequately addressed under the current Civil Code, resulting in unfair fare systems, insufficient driver protection, and unequal licensing practices. The main findings indicate the need for clear and cohesive legal instruments that ensure equal legal standing for all stakeholders. The study contributes to legal scholarship by proposing a revised partnership model rooted in legal certainty and social justice principles. It recommends regulatory harmonization, restructuring the partnership framework to reflect equitable legal positions, and implementing responsive legal standards. These steps are essential for developing a fair, sustainable, and inclusive transportation ecosystem in Indonesia.